(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
(IM)Posições is a dance show that develops from the mixture of parkour and dance techniques as a way to explore movements and the physical resistance of the dancers’ bodies, unfolding between techniques and themes of today’s society. The work dialogues directly with the social impositions imposed on individuals, taking into account the problems between bodies and their relationships in society, using lighting to create environments, scenes, and determine spaces.